PENGEMBANGAN MEDIA PEMBELAJARAN JAM SUDUT PADA PEMBELAJARAN MATEMATIKA SISWA KELAS IV SD NEGERI 12 LUBUKLINGGAU - Ria Mayasari Ria; Andriana Sofiarini; R. Angga Bagus Kusnanto (Sangkalemo : The Elementary School Teacher Education Journal, 2022)
This study aims to develop a product in the form of corner clock learning media in fourth grade mathematics learning at SD Negeri 12 Lubuklinggau in accordance with the 2013 curriculum and to produce a corner clock learning media that is valid, practical, and has effectiveness in the learning process. This research is a development research with a 4D development model. Based on the results of the validation analysis by the three experts, namely: linguists, material experts, and media experts, it showed that the angle clock media on the angle material and its measurements met the criteria of high validity with an average score of 0.85. While the results of the analysis of the assessment sheet on the practicality of teachers and students consisting of a small group (small group) of 6 students and a large group of 20 people, it was found that the corner clock media met the practical criteria with an average score of 92%, and the results of the effectiveness analysis showed that after conducting posttest obtained completeness of learning outcomes 73% with good criteria. So it can be concluded that the corner clock learning media in mathematics learning meets the valid, practical, and effective criteria for use in learning.